Hérnias diafragmáticas traumáticas: revisão casuística - Almeida e Sousa, JP (2008)
AIMS: This study classifies cases of traumatic diaphragmatic hernias (TDH) in patients admitted to the Intensive Care Unit (ICU) of the Coimbra University Hospitals (HUC) from 1990 to 2004. METHODS: Retrospective analysis of 34 cases of TDH, studying anatomical location, place and time of diagnosis, complementary tests aiding diagnosis, herniated organs, associated traumatism, morbidity and mortality. RESULTS: Twenty-eight male and six female patients with an average age of 40.5 years +/- 20.5, average SAPS score 38.8. Average length of stay was 19.1 +/- 13.6 days, all suffered from closed traumatism and were put on artificial ventilation. The left-side diaphragm was more frequently affected (94.1%) then the right. Diagnosis in 19 cases was made up in the first six hours following the diagnosis of traumatism, in four cases within 12 hours and in the remaining cases between 48 hours and 16 years after traumatism. In 13 patients the diagnosis was established intra-operatively. The stomach was typically one of the herniated organs. The most frequently associated lesions at the thoracic level were pulmonary contusion, haemothorax and pneumothorax, and at the abdominal level, haemoperitoneum and splenic lesion. The rates for complications and mortality were 55.8% and 11.7% respectively. CONCLUSIONS: TDH mainly occurs on the left side through closed thoraco-abdominal trauma following road traffic accidents. This group of patients, on average younger than others admitted to ICU, presents a longer average hospitalisation period, but has lower rates of mortality and lower SAPS severity scores. The most commonly herniated organ was the stomach and the most frequently encountered lesions were cranial-encephalic, splenic and pleural traumatisms. Pre-operative diagnosis of diaphragmatic injuries is difficult and a high index of clinical suspicion is needed after thoraco-abdominal trauma. This diagnosis should always be considered a possibility in cases of closed thoraco-abdominal traumas.